2011
DOI: 10.1038/mp.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 receptor, but not the ADHD-associated D4.7 variant, forms functional heteromers with the dopamine D2S receptor in the brain

Abstract: Polymorphic variants of the dopamine D4 receptor have been consistently associated with attention-deficit hyperactivity disorder (ADHD). However the functional significance of the risk polymorphism (variable number of tandem repeats in exon 3) is still unclear. Here we show that whereas the most frequent 4-repeat (D4.4) and the 2-repeat (D4.2) variants form functional heteromers with the short isoform of the dopamine D2 receptor (D2S), the 7-repeat risk allele (D4.7) does not. D2 receptor activation in the D2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 32 publications
3
111
0
Order By: Relevance
“…For example, ligand-based fluorescence resonance energy transfer studies identified oxytocin homodimers in rat mammary gland tissue (Albizu et al, 2010), and heterodimers of D 1 and D 2 dopamine receptors in striatal neurons are inferred from antibody-based fluorescence resonance energy transfer in fixed brain slices (Hasbi et al, 2011). Supporting evidence is provided by studies using heterodimer-selective antibodies (Berg et al, 2012) and transgenic mice expressing mutant receptors that restore (Rivero-Müller et al, 2010) or inhibit (González et al, 2012) normal receptor function. Pharmacological approaches have used heterodimer-selective agonists (Waldhoer et al, 2005;Fujita et al, 2014) or antagonists that bind in a pseudo-irreversible manner to one protomer within the homodimer (Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…For example, ligand-based fluorescence resonance energy transfer studies identified oxytocin homodimers in rat mammary gland tissue (Albizu et al, 2010), and heterodimers of D 1 and D 2 dopamine receptors in striatal neurons are inferred from antibody-based fluorescence resonance energy transfer in fixed brain slices (Hasbi et al, 2011). Supporting evidence is provided by studies using heterodimer-selective antibodies (Berg et al, 2012) and transgenic mice expressing mutant receptors that restore (Rivero-Müller et al, 2010) or inhibit (González et al, 2012) normal receptor function. Pharmacological approaches have used heterodimer-selective agonists (Waldhoer et al, 2005;Fujita et al, 2014) or antagonists that bind in a pseudo-irreversible manner to one protomer within the homodimer (Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…Nevertheless, some studies indicate a differential dependence of D2SR and D2LR on Gai/o protein subunits for agonist-induced signaling (Gardner et al, 1996;Xu et al, 2002). Although initial studies seemed to indicate that the D4.7R signals with less efficiency than the most common variant D4.4R (Asghari et al, 1995;Jovanovic et al, 1999), more recent studies suggest that their differences might arise from specific protein interactions, including dopamine receptor heteromerization (González et al, 2012b;Ferré et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Human glioblastoma T98G cells endogenously expressing CB 2 R and GPR55 (at similar levels as BT474 cells) 7 or stably transfected with selective CB 2 R or GPR55 shRNAs (Genecopoeia, Rockville, MD) and selected by FACS were grown in DMEM supplemented with 2 mM L-glutamine, 100 g/ml sodium pyruvate, 100 units/ml penicillin/streptomycin, minimal essential medium non-essential amino acid solution (1/100), and 10% (v/v) heatinactivated FBS in the presence of the corresponding selection antibiotic (5 g/ml puromycin for T98G-shGPR55 and T98G-shCB 2 ). For transient transfections, HEK293 and BT474 cells were transfected with the corresponding fusion protein cDNA by the PEI (Sigma) method (18).…”
Section: Methodsmentioning
confidence: 99%